Forecast of labor supply in the context of labor market modernization in Kazakhstan (Journal of Economic Research & Business Administration, 2018)
The importance of studying the current problems of the labor market is due to the fact that theproclaimed course of the third modernization of Kazakhstan involves ensuring dynamic growth of theeconomy based on its accelerated technological modernization and, accordingly, the creation of a fullyfunctioning labor market. Until now, the essence and content of the modernization of the labor marketand the influence of various factors on the dynamics of its development are not fully reflected in domesticscience. Particularly, there is the question of the degree of state intervention in the processes of labormarket regulation.In the new conditions, the modernized labor market, in turn, should become a factor of economicgrowth. In this regard, it is advisable to critically rethink the methods of analyzing and forecasting laborsupply and labor demand, mechanisms for the formation of wages and the functioning of labor marketinstitutions and other issues that characterize the current state of the labor market in the country. Thesituation on the labor market in Kazakhstan is largely determined by the imbalance of labor supply anddemand for labor. In this regard, it is important to determine the factors determining the relationshipbetween them.This article deals with the problems of labor supply formation (CP) in the Kazakhstan labor marketunder the influence of various factors. Their study is important both in theoretical and in practical terms.Numerous studies of the labor market focus on two main macroeconomic indicators — GDP and unemployment(employment), and unfairly little space is devoted to studying the supply of labor. Meanwhile,it is the quantitative and qualitative characteristics of the ORS and their comparison with the demand forlabor determine the direction and content of measures to achieve a balance between them.Methodology of research. The methodological basis of the problems discussed in the article arethe studies of foreign and domestic scientists on this problem. Due to the impossibility of covering theentire set of complex labor market issues, this article focuses on the study of the problem of forecastinglabor supply in the labor market in Kazakhstan. Based on the general laws governing the functioning ofthe labor market, the volume of labor supply is analyzed and projected depending on the influence ofvarious factors that reflect the specific conditions of economic development and the particularities of theKazakhstani model of the labor market. On the basis of a comparative analysis of the use of a number oftechniques, a specific method for predicting an ORS was proposed, the approbation of which on materialsfrom Kazakhstan confirmed the high accuracy of the forecast of the indicator under consideration.Our analysis was carried out on the basis of statistical data of the Committee on Statistics of theMinistry of National Economy of the Republic of Kazakhstan, reflecting the development of the country’seconomy for 2005-2016. The choice of this period of time from a methodological position is also notaccidental, it was during this period that the country’s economy experienced two crises with an intervalof 6-8 years, which in principle is characteristic of a market economy.At the same time, the problem of searching for a new model of economic growth was clearly revealed.Accelerated technological modernization of the economy is recognized as the main priority inthe implementation of the third modernization of Kazakhstan, which implies the mobilization of otheropportunities, including the modernization of the labor market. In order for the modernized labor marketto really become a factor of dynamic growth of the economy, it is necessary to achieve an accurateforecast of labor market indicators, in particular, the demand and supply of labor. This will reduce managementcosts, provide targeted social support to the unemployed and prevent social tensions in society.